Solar Powered Automated Waste Restraining Device for Sewages - Ruby Rosa N. Puno; Kristine E. Pineda; Jan Michael P. Canlas; Erick Carl G. Leabres; Anton Micael O. Mallari; Marvin S. Mallari; Mark Allen L. Manlutac (Southeast Asian Journal of Science and Technology, 2023)
In the community, waste is the reason why small-scale sewages or canals are clogging. It is also one of the reasons why floods and long-term floods occur. The study aims to mitigate these specific problems. The research study strived to develop a device specifically for restraining waste floating on a small-scale sewage or canal. Clogged sewage is a blockage of the drainage system that causes the water not to drain, resulting in frequent back-ups such as floods. Blockages are often caused by debris like plastic, dried leaves, pet bottles, etc. The researchers came up with a solution that can help collect substances from clogged sewage to avoid future setbacks. The study proposed a device named "Solar Powered Automated Waste Restraining Device for Sewages." This equipment will prevent the sewages from clogging by restraining and collecting debris on a free-flowing canal using an ultrasonic sensor. This device will automatically send notifications using the GSM module to authorized personnel to repeat the process until the sewage system is clogged-free. To strengthen the effectiveness of the device, the researchers tested the equipment for at least three days to see if it could efficiently lessen the cause of sewage blockages. Keywords — Small-scale Sewage, Waste Restraining Device, Drainage System, GSM Module, Ultrasonic Sensor.